Transverse dimension maxillary arch smile aesthetics comparison in non-extraction and extraction in Class I Angle malocclusion - Amalia, Fatimah Nur; Winoto, Ervina Restiwulan; Alfiandini, Ratna Nurlia (Faculty of Dental Medicine Universitas Airlangga, 2025)
Background: Malocclusion may affect aesthetic facial profile, and oral health-related quality of life. There are two orthodontic treatments to improve the facial profile, especially the aesthetics of the transverse dimension maxillary smile aesthetic (TDMASA), namely, extraction and non-extraction in the orthodontic treatments. Purpose: This study was conducted in order to compare extraction and non-extraction in orthodontic treatment on the aesthetics of TDMASA variables in patients with Class I Angle type 1 malocclusion at Dental Hospital / Rumah Sakit Gigi dan Mulut Pendidikan (RSGMP,) Universitas Airlangga (UNAIR) in the period 2017-2024. Methods: There were 19 extraction samples and 33 non-extraction samples, taken by means of total sampling technique. Intercanine Width (ICW) and Inter Molar Width (IMW) were measured using digital calipers. Smile width (SW) and maximum dental width (MDW) were measured using ImageJ software. Data analysis used a paired t-test to determine the difference in ICW, IMW, SW, and MDW and the ratio of ICW/SW, ICW/MDW, and MDW/SW before and after extraction and non-extraction treatments and an independent t-test to compare the results of ICW, IMW, SW, and MDW and the ratio of ICW/SW, ICW/MDW, and MDW/SW between extraction and non-extraction treatments. Results: There was a significant increase in ICW, IMW, SW, MDW, and MDW/SW ratio, and a significant decrease in ICW/SW and ICW/MDW in the extraction group (P<0.05). Conclusion: There was a significant difference in extraction and non-extraction case in orthodontic treatment on the aesthetics of TDMASA variables in patients with Class I Angle type 1 malocclusion.